Regional autonomy with regard to innovation policy: A differentiated illustration of the European status quo - Elisabeth Baier; Henning Kroll; Andrea Zenker (Fraunhofer Institute for Systems and Innovation Research ISI, 2013)
The EU wide differences in regional autonomy that we can observe today are based on comparatively recent developments which have occurred in parallel in a number of nations. In general, we found that the conception of a relevant quantitative reference framework for future research is not an easy task. Against this background, the main merit of our analysis may not lie in the overall index as such but in its composite parts. Moreover, our findings have been complemented by an illustration of different national cases to underline that the constitution of regional autonomy is a dynamic process that develops against different backgrounds and in different directions. (...)
urn:nbn:de:0011-n-2347654
Keywords: 330